A review of NMR methods used in the study of the structure and dynamics of ionic liquids. (16th November 2017) - Nanda, R.; Damodaran, Krishnan
Abstract : Recently, NMR spectroscopy has been emerging out as a powerful tool to study the structure and dynamics of ionic liquids (ILs) and ILs‐Li + salt mixtures. This mini‐review primarily focuses on the applications of various NMR spectroscopic techniques such as self‐diffusion measurements, NMR relaxometry, two‐dimensional NMR, and other novel NMR approaches to study the structure and dynamics of ILs and its mixtures with lithium salts. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : This mini‐review presents applications of various NMR spectroscopic methods used in the study of structural and dynamical aspects of ionic liquids and its mixtures with various lithium salts.